In silico design and evaluation of novel cell targeting melittin-interleukin-24 fusion protein: a potential drug candidate against breast cancer - Rehman, Hafiz Muhammad; Rehman, Hafiz Muzzammel; Ahmed, Nadeem; Amirzada, Muhammad Imran; Aslam, Shakira; Bashir, Hamid (Penerbit Universiti Kebangsaan Malaysia, 2023)
Fusion proteins are designed to achieve new functionality or improved properties synergistically by incorporating multiple protein domains into one complex. The fusion of two genes to translate a recombinant protein for cancer treatment can enhance the bioactivity of drug and can introduce novel drug candidate with wide range of applications in pharmaceuticals and biotechnology. Interleukin-24 (IL-24) is a novel cancer growth-suppressing and apoptosis inducing cytokine while melittin is a natural honeybee derived cationic polypeptide having anti-tumor activity against breast cancer cells. The current study was aimed to perform in silico design and analyses of a melittin-IL-24 fusion protein against breast cancer. The amino acid sequences of the IL-24 and melittin peptide were used to design the fusion protein via a rigid linker. Using the online softwares we predicted the secondary and tertiary structures along with physicochemical properties of the designed fusion protein. The validation and quality of the fusion protein was confirmed by Rampage and ERRAT2. The top ranked structure from I-TASSER showed 18.1KD molecular weight by ProtParam, quality factor of 94.152 by ERRAT and a valid structure by Ramachandran plot with 88.5% residues in favoured region. The docking and simulation studies were performed using ClusPro and Desmond software. The quality, validity, interaction analysis and stability of the fusion protein depicted a functional molecule. The in silico analysis finding and expression predicted value of 0.86 in E. coli on SOLUPROT tool suggest that the melittin- IL-24 fusion protein can lead to develop a potent therapeutic drug against breast cancer.